Digital television : a practical guide for engineers. - Fischer, Walter, 1961- (Berlin : Springer, 2004)
Digital Television deals with all present-day TV transmission methods, i.e. MPEG, DVB, ATSC and ISDB-T. The DVD Video is also discussed to some extent. The discussion is focussed on dealing with these subjects in as practical a way as possible. Although mathematical formulations are used, they are in most cases only utilized to supplement the text. The book also contains chapters dealing with basic concepts such as digital modulation or transformations into the frequency domain. A major emphasis is placed on the measuring techniques used on these various digital TV signals. Practical examples and hints concerning measurement are provided. The book starts with the analog TV baseband signal and then continues with the MPEG-2 data stream, digital video, digital audio and the compression methods. After an excursion into the digital modulation methods, all the mentioned transmission methods are discussed in detail. Interspersed between these are found the chapters on the relevant measuring technique.
Keywords: Digitale televisie